The Impact of EBV Status on Characteristics and Outcomes of Posttransplantation Lymphoproliferative Disorder. Issue 10 (18th May 2015) - Luskin, M. R.; Heil, D. S.; Tan, K. S.; Choi, S.; Stadtmauer, E. A.; Schuster, S. J.; Porter, D. L.; Vonderheide, R. H.; Bagg, A.; Heitjan, D. F.; Tsai, D. E.; Reshef, R.
<x xml:space="preserve">Abstract</x> We examined the associations of Epstein–Barr virus (EBV) status with characteristics and outcomes of posttransplantation lymphoproliferative disorder (PTLD) by studying 176 adult solid organ transplant recipients diagnosed with PTLD between 1990 and 2013 (58 [33%] EBV‐negative; 118 [67%] EBV‐positive). The proportion of EBV‐negative cases increased over time from 10% (1990–1995) to 48% (2008–2013) (p < 0.001). EBV‐negative PTLD had distinct characteristics (monomorphic histology, longer latency) though high‐risk features (advanced stage, older age, high lactate dehydrogenase, central nervous system involvement) were not more common compared to EBV‐positive PTLD. In multivariable analysis, EBV negativity was not significantly associated with worse response to initial therapy (adjusted odds ratio, 0.84; p = 0.75). The likelihood of achieving a complete remission (CR) was not significantly different for EBV‐negative versus EBV‐positive PTLD including when therapy was reduction of immunosuppression alone (35% vs. 43%, respectively, p = 0.60) or rituximab (43% vs. 47%, p = 1.0). EBV negativity was also not associated with worse overall survival (adjusted hazard ratio, 0.91; p = 0.71). Our findings indicate that EBV status is not prognostic or predictive of treatment response in adults with PTLD. The high proportion of EBV‐negative disease diagnosed in recent years highlights the need for new strategies for prevention and management of EBV‐negative PTLD.